2016
DOI: 10.1158/1078-0432.ccr-15-2703
|View full text |Cite
|
Sign up to set email alerts
|

WRN Promoter CpG Island Hypermethylation Does Not Predict More Favorable Outcomes for Patients with Metastatic Colorectal Cancer Treated with Irinotecan-Based Therapy

Abstract: PURPOSE WRN promoter CpG island hypermethylation in colorectal cancer (CRC) has been reported to increase sensitivity to irinotecan-based therapies. We aimed to characterize methylation of the WRN promoter; determine the effect of WRN promoter hypermethylation upon expression; and validate a previous report that WRN promoter hypermethylation predicts improved outcomes for metastatic colorectal cancer (mCRC) patients treated with irinotecan-based therapy. DESIGN WRN methylation status was assessed using methy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(63 reference statements)
1
9
1
Order By: Relevance
“…Similar preclinical and early phase clinical studies in ovarian cancer have shown DNMTi reversing resistance to platinum agents (8). In preclinical CRC models, DNMTis can induce re-expression of tumor suppressor genes (9). Our group has reported DNMTi can both induce sensitivity and reverse chemoresistance to irinotecan in in vitro and in vivo models (10).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar preclinical and early phase clinical studies in ovarian cancer have shown DNMTi reversing resistance to platinum agents (8). In preclinical CRC models, DNMTis can induce re-expression of tumor suppressor genes (9). Our group has reported DNMTi can both induce sensitivity and reverse chemoresistance to irinotecan in in vitro and in vivo models (10).…”
Section: Introductionmentioning
confidence: 79%
“…There is no well-agreed upon mechanism that has explained irinotecan resistance (23,24). It has been hypothesized that that methylation of DCR1 and WRN, the latter being a DNA helicase, may affect sensitivity to irinotecan, but confirmatory studies to validate these findings in clinical data sets have not been successful (9,(25)(26)(27). The multifocal effects of epigenetic therapies, such as guadecitabine, that result in widespread changes in gene expression across hundreds of cellular pathways, may well be responsible for reversing resistance to cytotoxic chemotherapies, but also create great barriers in understanding the mechanisms behind these effects (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Hypomethylating agents can reverse this resistance mechanism by promotor demethylation and subsequent gene expression reactivation (Lee et al, 2018). In fact, tumor suppressor genes were found re-expressed by DNA methyltransferase enzyme inhibitors (DNMTi) in colorectal cancer cell lines (Bosch et al, 2016). In line with this, DNMTinhibitors-reversed irinotecan chemotherapy resistance in colorectal cancer models, in vitro and in vivo (Sharma et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Irinotecan (CPT-11), a semi-synthetic derivative of CPT, which is routinely used in colorectal cancer therapy, enhances the survival of colorectal cancer patients with hypermethylated WRN promoter 90 . In contrast, Bosch et al reported that hypermethylation of the WRN promoter does not have predictive value for personalized irinotecan-based therapy 91 . The observed differences could be due to the complex nature of promoter hypermethylation and varied expression of WRN.…”
Section: Wrn In Cancer Researchmentioning
confidence: 93%
“…Primary tumors of colorectal cancer patients and cell lines display decreased WRN mRNA and protein expression 90 , 91 ; however, no WRN mutations have been associated with colorectal cancer risk 92 , 93 . Irinotecan (CPT-11), a semi-synthetic derivative of CPT, which is routinely used in colorectal cancer therapy, enhances the survival of colorectal cancer patients with hypermethylated WRN promoter 90 .…”
Section: Wrn In Cancer Researchmentioning
confidence: 99%